The Molecular Mechanism of B Cell Activation by toll-like Receptor Protein RP-105 - Chan, Vivien W.F. (The Rockefeller University Press, 1998)

(untitled)
The B cell–specific transmembrane protein RP-105 belongs to the family of Drosophila toll-like proteins which are likely to trigger innate immune responses in mice and man. Here we demonstrate that the Src-family protein tyrosine kinase Lyn, protein kinase C β I/II (PKCβI/II), and Erk2-specific mitogen-activated protein (MAP) kinase kinase (MEK) are essential and probably functionally connected elements of the RP-105–mediated signaling cascade in B cells. We also find that negative regulation of RP-105–mediated activation of MAP kinases by membrane immunoglobulin may account for the phenomenon of antigen receptor–mediated arrest of RP-105–mediated B cell proliferation.